Effect of different doses of nitrogen and sulphur on growth, yield and quality of onion (Allium cepa) - JAIN, GOLDI; KUSHWAH, S S; SINGH, O P; VERMA, K S (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the rabi season of 2009-10 at research farm, College of Horticulture, Mandsaur (Madhya Pradesh) to study the effect of different dose of nitrogen and sulphur on growth, yield and quality of onion. The treatments consisted of three levels of nitrogen, viz. N1 - 80 kg N/ ha, N2 -100 kg N/ha and N3- 120 kg N/ha and four levels of sulphur, viz. S1-15 kg S/ha, S2- 30 kg S/ha, S3- 45 kg S/ha and S4 - 60 kg S/ha. Application of nitrogen and sulphur had significant influence on the growth, yield and quality attributes of onion. Maximum plant height, number of leaves per plant, fresh weight of shoot, fresh weight of bulb, horizontal diameter, vertical diameter, bulb yield, neck diameter, total soluble solid content and pyruvic acid content were recorded with application of nitrogen 120 kg/ha. Similarly application of 60 kg S/ha resulted in highest values of growth, yield and quality attributes of onion. Combined effect of nitrogen and sulphur showed significant effect on fresh weight of shoot, fresh weight of bulb, horizontal diameter, vertical diameter, bulb yield and pyruvic acid content with maximum values under 120 kg N + 60 kg S/ha. Maximum gross income, net income and cost: benefit ratio was also found with 120 kg N + 60 kg S/ha.